2017
DOI: 10.11138/mltj/2017.7.1.152
|View full text |Cite
|
Sign up to set email alerts
|

Chondrocytes treated with different shock wave devices

Abstract: SummaryBackground: Shock wave treatment is used for several orthopedic diseases and there are different devices available. Until now, there have been no experimental studies on the effects of these different generators. Methods: We carried out an experimental study to compare the effects of three focused generators (electro-magnetic, piezoelectric and electro-hydraulic) as well as a radial generator on healthy and osteoarthritis chondrocytes. Results: By the analysis of our results, we may exclude significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…But all of they suggested that shock wave can serve as one of the treatments on KOA. [710] Notarnicola et al [11] had verified through in vitro cell experiment that, ESWT could upregulate the expression of IL-10, while down-regulating that of N-cadherin and β-catenin. Yilmaz et al [12] had treated the KOA rats through ESWT and confirmed that, ESWT could promote the proliferation and regeneration of cartilage tissues in rats.…”
Section: Introductionmentioning
confidence: 99%
“…But all of they suggested that shock wave can serve as one of the treatments on KOA. [710] Notarnicola et al [11] had verified through in vitro cell experiment that, ESWT could upregulate the expression of IL-10, while down-regulating that of N-cadherin and β-catenin. Yilmaz et al [12] had treated the KOA rats through ESWT and confirmed that, ESWT could promote the proliferation and regeneration of cartilage tissues in rats.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that ESWT increased the expression of IL-10 (responsible for inhibiting the production of pro-inflammatory cytokines). In contrast, it decreased the expression of both N-cadherin and b-catenin (their upregulation is responsible for the degeneration) 49 . Further, knee pain as a sequela of OA is a primary complaint of the affected individuals; in several cases, the pain becomes difficult to subside with even medications and non-pharmacological interventions 50 52 .…”
Section: Discussionmentioning
confidence: 96%
“…Only one medication (oral prednisolone 10 mg/day) has a greater symptomatic effect than placebo, but raises safety issues [6]. Thus, there is a strong need for therapeutic innovation in EHOA, especially non-pharmacological therapies [7].…”
Section: Introductionmentioning
confidence: 99%